2019
DOI: 10.1002/acr2.11061
|View full text |Cite
|
Sign up to set email alerts
|

External Validation and Evaluation of Adding MRI or Extended Myositis Antibody Panel to the 2017 EULAR/ACR Myositis Classification Criteria

Abstract: Objective. To externally validate the European League Against Rheumatism/American College of Rheumatism (EULAR/ACR) classification criteria for idiopathic inflammatory myositis (IIM) and determine the optimal cut points for Australian patients. To determine the level of agreement with traditional criteria and assess the effect of including magnetic resonance imaging (MRI) and an extended myositis antibody panel as well as extending histological criteria to include myofiber invasion. Methods. Data were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 12 publications
0
26
1
Order By: Relevance
“…4 The final complete analysis was presented to an international audience at the October 2018 American College of Rheumatology Annual Scientific meeting 5 and published in ACR Open Rheumatology online in August 2019. 7 We found that in our cohort the EULAR/ACR criteria had very high specificity but lower sensitivity, and lower optimal sensitivity and specificity cut points than that suggested in the EULAR/ACR report. We also explored the effect of MRI and an extended panel of myositis-associated antibodies and MSAs and showed in a logistic regression model that including them as covariates of the EULAR/ACR criteria improved the ability to discriminate between IIM and non-IIM patients.…”
Section: External Validation Of Eular/acr Classification Criteria Forcontrasting
confidence: 65%
“…4 The final complete analysis was presented to an international audience at the October 2018 American College of Rheumatology Annual Scientific meeting 5 and published in ACR Open Rheumatology online in August 2019. 7 We found that in our cohort the EULAR/ACR criteria had very high specificity but lower sensitivity, and lower optimal sensitivity and specificity cut points than that suggested in the EULAR/ACR report. We also explored the effect of MRI and an extended panel of myositis-associated antibodies and MSAs and showed in a logistic regression model that including them as covariates of the EULAR/ACR criteria improved the ability to discriminate between IIM and non-IIM patients.…”
Section: External Validation Of Eular/acr Classification Criteria Forcontrasting
confidence: 65%
“…Response to: 'External validation of EULAR/ACR classification criteria for idiopathic inflammatory myopathies' by Luu et al We would like to thank Luu et al 1 for their comments on our recent publication in the Annals of the Rheumatic Diseases, entitled 'First external validation of sensitivity and specificity of the European League Against Rheumatism (EULAR)/American College of Rheumatology (ACR) classification criteria for idiopathic inflammatory myopathies with a Japanese cohort'. 2 We are pleased to know similar validation studies of the new criteria [3][4][5][6][7] have been carried out to strengthen our contention. Although Luu et al 1 argue that earlier studies have been published before ours, they were not found with the PubMed search, using the name of the new criteria and validation as keywords, at the time of the submission of our manuscript in April 2019.…”
mentioning
confidence: 58%
“…Before our publication, Luu et al gave their presentation in scientific meetings in 2018, 3 4 which was followed by an official publication in the middle of 2019. 5 It is common that presentations at scientific meetings precede the final and formal publication. The meeting abstracts do not appear in the literature databases, reflecting their possible scientific immaturity.…”
mentioning
confidence: 99%
“…While a caveat to the high concordance between the 2017 EULAR/ACR criteria and the Bohan and Peter criteria (95.8% for PM patients and 83.7% for DM patients) demonstrated by Yoo et al [ 7 ] may be that the sample size was too small to represent IIM Korean patients generally, this finding could be of value in clinical research and in the diagnosis of patients in routine clinical practice in Korea. Currently, the focus of attention is on variables such as MSA antibodies and magnetic resonance imaging findings, which have shown promise in the early diagnosis of IIM and in assessing the treatment response [ 11 ]. The development of new classification criteria based on the most up-to-date information, and applicable not only in clinical research but also in clinical practice, is eagerly awaited.…”
mentioning
confidence: 99%